2016
DOI: 10.1292/jvms.16-0205
|View full text |Cite
|
Sign up to set email alerts
|

Functional validation of tensin2 SH2-PTB domain by CRISPR/Cas9-mediated genome editing

Abstract: Podocytes are terminally differentiated and highly specialized cells in the glomerulus, and they form a crucial component of the glomerular filtration barrier. The ICGN mouse is a model of glomerular dysfunction that shows gross morphological changes in the podocyte foot process, accompanied by proteinuria. Previously, we demonstrated that proteinuria in ICR-derived glomerulonephritis mouse ICGN mice might be caused by a deletion mutation in the tensin2 (Tns2) gene (designated Tns2nph). To test whether this mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 37 publications
1
18
0
Order By: Relevance
“…Tensin that contains integrin binding region is known as cytoskeleton linker protein and signal transducer [Lo et al., ]. Growing body of evidence has shown that tensin2 is a relevant for the maintenance of normal kidney function [Lo et al., ; Cho et al., ] Moreover, tensin mutation or deficiency in mice have been indicated to alterate of actin remodelling in podocytes, which results in foot process effacement and massive albuminuria [Marusugi et al., ; Takahashi et al., ]. Tensins are close relatives of phosphatase and tensin homolog (PTEN).…”
Section: Impact Of Ampk On Podocyte Actin Cytoskeletonmentioning
confidence: 99%
“…Tensin that contains integrin binding region is known as cytoskeleton linker protein and signal transducer [Lo et al., ]. Growing body of evidence has shown that tensin2 is a relevant for the maintenance of normal kidney function [Lo et al., ; Cho et al., ] Moreover, tensin mutation or deficiency in mice have been indicated to alterate of actin remodelling in podocytes, which results in foot process effacement and massive albuminuria [Marusugi et al., ; Takahashi et al., ]. Tensins are close relatives of phosphatase and tensin homolog (PTEN).…”
Section: Impact Of Ampk On Podocyte Actin Cytoskeletonmentioning
confidence: 99%
“…SNP rs73099903 was in strong linkage disequilibrium (LD r 2 >0.9) with the SNP most strongly associated with TNS2 expression in the BIOS resource. TNS2 encodes a tensin focal adhesion molecule and may have a role in renal function (26).…”
Section: Resultsmentioning
confidence: 99%
“…The ICGN mouse, an animal model for nephrotic syndrome, shows severe proteinuria and glomerulosclerosis with impairment of nephrin and synaptopodin 35 . Also, podocyte abnormalities and proteinuria are observed in mice with C1-Ten SH2-PTB domain deletion mutant 36 . These results and our study suggest that both C1-Ten WT overexpression and C1-Ten mutation contribute to podocyte dysfunction and proteinuria.…”
Section: Discussionmentioning
confidence: 98%